DIFFERENTIAL WEALTH OF POLISH MUNICIPALITIES AND QUALITY OF LIFE IN MUNICIPALITIES – SELECTED CORRELATIONS AND MANAGEMENT IMPLICATIONS - Śmietanko, Tomasz (Management and Administration Journal, 2024)
The purpose of this article is to identify the relationship between the wealth of Polish municipalities and the quality of life in municipalities and, on this basis, to formulate conclusions and recommendations for municipal management. Although the impact of the wealth of municipalities on quality of life seems quite obvious, on the basis of the review of the literature to date, such relationships are unlikely to have been the subject of detailed scientific analysis. The subject of this study was Polish urban-rural municipalities that are also district cities. The study measured the correlation between the financial situation of municipalities in three groups: the most affluent, medium affluent, and least affluent and the quality of life, expressed on the basis of 78 detailed indicators of the Central Statistical Office. The study shows a strong correlation between the wealth of municipalities and the overall quality of life in municipalities and a statistically significant, differentiated, overall quality of life in the three groups of municipal wealth, as well as the different strength of the impact of municipal wealth on the identified four segments of quality of life: economic, social, environmental, and institutional-political.